Assessing the effects of hydrogen peroxide bleaching agent on the shear bond strength of orthodontic brackets - Augusto Ricardo Andrighetto; Eduardo Henrique de Leão Withers; Karlos Giovani Grando; Aldrieli Regina Ambrosio; Roberto Hideo Shimizu; Ana Cláudia Melo (Wolters Kluwer Medknow Publications, 2016)
Background: Tooth bleaching is, today, one of the most widespread cosmetic treatments in dental practice,  so it is important to determine whether it can interfere with orthodontic bonding or not. Aim: The aim of this study was to assess the in vitro effects of 35% hydrogen peroxide bleaching agent on the shear bond strength of orthodontic brackets. Materials and Methods: Forty-five upper bicuspids were divided into three groups (n = 15). In the control Group (C), the brackets were bonded without previous bleaching treatment. Group 1 (G1) was treated with 35% hydrogen peroxide bleaching agent 24 h before bracket bonding. Group 2 was also bleached, and the brackets were bonded after 30 days. The shear bond strength of the brackets was measured using an EMIC machine, and the results were analyzed by ANOVA. Results: There were no statistically significant differences between the three groups (P > 0.05), with Group C showing a mean bond strength of 9.72 ± 2.63 MPa, G1 of 8.09 ± 2.63 MPa, and G2 of 11.15 ± 4.42 MPa. Conclusion: It was possible to conclude that 35% hydrogen peroxide bleaching agent does not affect the shear strength of orthodontic brackets bonded 24 h and 30 days after bleaching.